Attitudes of Iranians Living in North Cyprus Towards Iranian Cinema - Ghashghaeiabdi, Ramtin (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2023)
This study explores the relationship between Iranian cinema, social movements, and the experiences of Iranian immigrants in North Cyprus. Its primary aim is to investigate whether Iranian cinema accurately represents social movements, discern the perspectives of Iranian immigrants, and assess the influence of Iranian cinematic narratives on public sentiment and collective mobilization. The research seeks to understand if Iranian immigrants perceive Iranian cinema as an authentic portrayal of social movements in Iran, examining their viewpoints on these cinematic depictions and their resonance with personal experiences. Additionally, it explores how Iranian cinema may shape public opinion, raise awareness, and inspire collective action among Iranian immigrants in North Cyprus. This reveals the dynamic interaction between cinematic representations and the motivations, challenges, and identities of social movement participants. It also demonstrates how these cinematic narratives align with the experiences and identities of Iranian immigrants, impacting their perceptions and motivations for involvement in social causes. This research contributes to cinema studies, social movements, and the immigrant experience, offering practical insights for cultural initiatives, community engagement strategies, and policies to empower immigrant populations. It recognizes cinema as a potent medium for intercultural dialogue, enhancing social cohesion and mobilizing communities toward collective action. Through a diaspora theory lens, this study sheds light on how cinematic narratives reflect and influence the collective consciousness and engagement of Iranian immigrants in their pursuit of social change.

ÖZ: Bu çalışma, İran sineması, toplumsal hareketler ve Kuzey Kıbrıs'ta yaşayan İran göçmenlerinin deneyimleri arasındaki ilişkiyi incelemektedir. Temel amacı, İran sinemasının toplumsal hareketleri doğru bir şekilde temsil edip etmediğini araştırmak, İran göçmenlerinin perspektiflerini anlamak ve İran sinemasının kamusal görüşü ve kolektif hareketi nasıl etkilediğini değerlendirmektir. Araştırma, İran göçmenlerinin İran sinemasını, İran'daki toplumsal hareketlerin otantik bir tasviri olarak algılayıp algılamadığını anlamayı amaçlamaktadır. Bu sinemasal tasvirler üzerindeki görüşlerini ve bu tasvirlerin kişisel deneyimleriyle ne kadar örtüştüğünü incelemektedir. Ayrıca çalışma, İran sinemasının Kuzey Kıbrıs'ta yaşayan İran göçmenleri arasında kamusal görüşü nasıl şekillendirebileceğini, farkındalık yaratabileceğini ve kolektif eylemi nasıl teşvik edebileceğini incelemektedir. Bu araştırma, sinema çalışmaları, toplumsal hareketler ve göçmen deneyimine katkı sağlayarak kültürel girişimler, toplum katılımı stratejileri ve göçmen nüfusunu güçlendirmeyi amaçlayan politikalar için pratik içgörüler sunmaktadır. Bu durum, sinemanın, kültürel diyaloğun güçlendirilmesi ve toplulukları kolektif eyleme doğru harekete geçirme konusunda etkili bir araç olarak kabul edildiği bir ortamda gerçekleşmektedir. Diaspora teorisi perspektifinden, bu çalışma, sinema anlatılarının İran göçmenlerinin kolektif bilincini ve katılımlarını nasıl yansıttığını ve etkilediğini incelemektedir.
Master of Arts in Communication and Media Studies. Institute of Graduate Studies and Research. Thesis (M.A.) - Eastern Mediterranean University, Faculty of Communication And Media Studies, 2023. Supervisor: Asst. Prof. Dr. Barçın Boğaç.
Keywords: Communication And Media Studies Department; Cinema--Motion pictures--Iran; Iranian Cinema--Motion pictures--Social aspects--Iran; Iranian cinema, social movements, Iranian immigrants, Cinematic narratives, Diaspora theory